SEORANG PENDERITA HEPATITIS B AKUT BERAT, MUTAN â€œPRECOREâ€, GENOTIP C, YANG DITERAPI DENGAN ENTECAVIR MENGALAMI KECURIGAAN SINDROMA GIANOTTI-CROSTI - Hendrata Erry Andisari (Oceana Biomedicina Journal, 2023)
Introduction: The clinical course of HBV is very dynamic and difficult to predict, it can survive in the liver without causing clinical symptoms, or transform into a mutant form with clinical manifestations of severe acute hepatitis B (HBA) or fulminant hepatitis. Case: Patient Mr. AS, 22 years old, came to a private clinic (West Surabaya) on January 22, 2022. Due to yellow eyes, since 1 week before the patient has complained of weakness, lack of appetite, muscle and joint pain, and body aches. Conclusion: Entecavir therapy in Severe HBA is safe, provides clinical improvement, accompanied by clearing of HBV DNA and rapid anti-HBs seroconversion occurs.